2021
DOI: 10.1108/cc-06-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Access control of human resource records: case of the University of Cape Coast, Ghana

Abstract: Purpose Security of human resource records is important because of their nature but they are not adequately managed. This study aims to investigate access control issues affecting the security and confidentiality of human resource records at the University of Cape Coast. Design/methodology/approach A qualitative approach was used to conduct the study. Purposive sampling was used to select staff at the Directorate of Human Resource, University of Cape Coast. A textual analysis was used in analysing responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…The strategies used in the maintenance of human resource records include protection from non-staff and dangers like rodents, tracking the movement of the records and adequate storage facilities. Regarding protection from non-staff, rodents and tracking of personal files, Andoh and Attafuah (2021) had similar results in their study. Generally, the findings prove that maintaining human resource records is a challenge in the University and that the staff are not well equipped to effectively maintain records in their custody.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The strategies used in the maintenance of human resource records include protection from non-staff and dangers like rodents, tracking the movement of the records and adequate storage facilities. Regarding protection from non-staff, rodents and tracking of personal files, Andoh and Attafuah (2021) had similar results in their study. Generally, the findings prove that maintaining human resource records is a challenge in the University and that the staff are not well equipped to effectively maintain records in their custody.…”
Section: Resultssupporting
confidence: 70%
“…In an access control of human resource records study by Andoh and Attafuah (2021), it was found that personal files were protected from unauthorised access and rodents. Also, they found that files that were moved could be traced in the file movement book.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are generated in parts by the employees themselves and the organization and when put together, are the basis for effective human resource planning and management (Johnson and Gueutal, 2011; Stanton and Weiss, 2003). Without human resource records, organizations will not have the required information on their employees to plan and manage (Andoh and Attafuah, 2022; Msuya and Lyaruu, 2008), and this will have dire consequences on their competitiveness and sustainability. In addition, human resource records largely serve the interest of employees (IRMT, 2009; Johnson and Gueutal, 2011; Msuya and Lyaruu, 2008; Stanton and Weiss, 2003).…”
Section: Theoretical Basis and Hypothesesmentioning
confidence: 99%
“…Even though it has been established that control measures are implemented to ensure the security of human resource records so that they are not accessed by people who do not have the right to access them (Andoh and Attafuah, 2022; Dewah and Ndlovu, 2013), Culnan and Armstrong (1999) have asserted that people who disclose personal information to organizations are at risk of the information being exposed to unintended third parties. Consequently, employees may remain quite skeptical about the provision, use and security of their personal information.…”
Section: Theoretical Basis and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation